2005
DOI: 10.1016/s0002-9440(10)62047-0
|View full text |Cite
|
Sign up to set email alerts
|

Activin Controls Skin Morphogenesis and Wound Repair Predominantly via Stromal Cells and in a Concentration-Dependent Manner via Keratinocytes

Abstract: The transforming growth factor-beta family member activin is a potent regulator of skin morphogenesis and repair. Transgenic mice overexpressing activin in keratinocytes display epidermal hyper-thickening and dermal fibrosis in normal skin and enhanced granulation tissue formation after wounding. Mice overexpressing the secreted activin antagonist follistatin, however, have the opposite wound-healing phenotype. To determine whether activin affects skin morphogenesis and repair via activation of keratinocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 46 publications
7
57
0
1
Order By: Relevance
“…These findings demonstrate that aberrant expression and activity of activin are associated with abnormal skin development and impaired wound healing and suggest that activin regulates migration, proliferation, and differentiation of many cell types in the skin, including keratinocytes. This was confirmed by our recent results, which demonstrated that activin receptor signaling in keratinocytes is important for hair follicle morphogenesis and wound re-epithelialization (Bamberger et al, 2005). In addition, a role of activin in the regulation of keratinocyte proliferation and differentiation was found in in vitro studies with keratinocyte monocultures, where a weak inhibitory effect of activin on keratinocyte proliferation and induction of keratinocyte differentiation by this factor was demonstrated (Shimizu et al, 1998;Seishima et al, 1999).…”
supporting
confidence: 84%
“…These findings demonstrate that aberrant expression and activity of activin are associated with abnormal skin development and impaired wound healing and suggest that activin regulates migration, proliferation, and differentiation of many cell types in the skin, including keratinocytes. This was confirmed by our recent results, which demonstrated that activin receptor signaling in keratinocytes is important for hair follicle morphogenesis and wound re-epithelialization (Bamberger et al, 2005). In addition, a role of activin in the regulation of keratinocyte proliferation and differentiation was found in in vitro studies with keratinocyte monocultures, where a weak inhibitory effect of activin on keratinocyte proliferation and induction of keratinocyte differentiation by this factor was demonstrated (Shimizu et al, 1998;Seishima et al, 1999).…”
supporting
confidence: 84%
“…Its soluble protein product follistatin binds and neutralizes members of the TGFb superfamily 15 , including activin, which is involved in scar formation in skin. Accordingly, mice overexpressing follistatin display reduced wound healing 18 , whereas overexpression of activin results in epidermal thickening and dermal fibrosis in normal skin and enhanced granulation tissue formation after wounding 32 . Our study in European subjects did not detect associations at either of the two previously described acne risk loci 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that activin promotes wound healing and chemically induced skin carcinogenesis, in particular by activating various types of stromal cells (10,12,13,29). Furthermore, other laboratories demonstrated that activin affects different types of immune cells in vitro and in vivo [reviewed by (29,30)].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we previously showed that transgenic mice overexpressing activin A in keratinocytes under control of the keratin 14 promoter (Act mice) are characterized by enhanced granulation tissue formation and accelerated reepithelialization after wounding, and also by enhanced skin carcinogenesis and malignant progression (10,12). Interestingly, acceleration of wound repair by activin is at least in part mediated via stromal cells (13). The role of the stroma in the protumorigenic effect of activin was even more remarkable, because inhibition of activin signaling in keratinocytes did not reduce tumorigenesis.…”
Section: Ast Cells Are Tissue-resident Cells and Well Known For Thementioning
confidence: 99%